Cornelia de Lange Syndrome Accompanied by Cholelithiasis and Nephrolithiasis: A Case Report - So Yoon Choi; Yoo-Rha Hong; Chi-Eun Oh; Jung Hyun Lee (Children)
Cornelia de Lange syndrome (CdLS) is a rare genetic disorder characterized by a distinctive facial appearance, growth/cognitive retardation, developmental delay, skeletal malformation, hypertrichosis, and other abnormalities. Patients with mild CdLS have less severe phenotypes, while retaining representative facial features. Mutations in the genes NIPBL, SMC1A, SMC3, HDAC8, and RAD21 have been associated with CdLS, with mutations in NIPBL accounting for approximately 60% of cases. Herein, we present a case of CdLS accompanied by cholelithiasis and nephrolithiasis. A 9-year-old Korean boy presented with vomiting and abdominal pain. Abdominal ultrasonography revealed several gallstones and renal stones. Extracorporeal shock wave lithotripsy failed; therefore, cholecystectomy and nephrolithotomy were performed. Postoperative stone composition analysis revealed calcium oxalate as the primary component. CdLS was suspected based on the characteristic appearance and physical examination, with genetic testing confirming an NIPBL gene mutation. Simultaneous CdLS, cholelithiasis, and nephrolithiasis requires careful management and treatment tailored to each patient’s specific needs and challenges.